Pelvic Incidence as a Prognostic Variable to Assess the Outcome of Conservative Treatment in the Patients with Spondylolisthesis. Issue 1 (April 2016) - Sai Krishna, M. L. V.; Sharma, Deep; Menon, Jagdish; Barathi, Deepak
Introduction: Spondylolisthesis is defined as slippage of one vertebra over the below one. Ever since the discovery of pelvic incidence by legaye et al. in 1998 and as well as documentation of the other parameters for spinopelvic balance, the slippage in listhesis has been attributed to these parameters. Many studies were done in the Caucasian population, which implicates high pelvic incidence as a causative factor for the listhesis. But to our knowledge, no study has described the implication of these parameters in the progression of listhesis. The main aim of our present study was to know the importance of the spinopelvic parameters in the causation and progression of the listhesis and also to know the response to conservative treatment. Materials and Methods : The study was approved by our institute review board and the ethical committee. We included all the patients visiting our OPD with complaints of LBP for more than three months, whose X-ray shows spondylolisthesis and who gave consent for the study. All patients were advised conservative treatment (NSAIDS, physiotherapy and short wave diathermy) and were followed once in 2 weeks regularly and were evaluated once in 6 weeks with the help of modified Oswestry questionnaire. At the end of 6 months, patients who were improved were advised the same conservative treatment and followed up. Those who have not improved were suggested repeat X-rays and the parameters and grade of listhesis recalculated. A total of 79 patients were thus included in the study. Another age and sex matched group of asymptomatic volunteers ( n = 75) were also recruited as a control group. Out of the total of 79 patients, 35 were followed for six month period of which 27 improved and in 8 there was no improvement. 25 have lost follow-up and in 19 follow-up was still pending. All the patients and volunteers underwent a standardized lateral sagittal digital radiograph of the whole spine including the base of the skull till the proximal ⅓ thigh. The sagittal spinopelvic parameters were measured using the Surgimap spine software version 2.1.2 by a single observer. The parameters measured were pelvic incidence PI, pelvic tilt PT, sacral slope SS, thoracic kyphosis TK, lumbar lordosis LL, lordotic and kyphotic vertebra. The comparisons were drawn between the patients and controls using appropriate statistical methods. Results: The mean values in the asymptomatic group are PI-47.85, PT-13.03, SS-34.8, LL-54.68, TK-24.03. In the listhesis group are PI-65.32, PT-21.30, SS-44.13, LL-54.08, TK-25.49. There was a significant difference between the normal and the listhesis groups among PI, SS, PT ( p < 0.001). There was no significant difference in pelvic incidence between the patients with high-grade(grade 3, 4, 5) and low-grade listhesis(grade 1, 2). Conclusion: The progression of slip and the response of the conservative treatment depends on- pelvic incidence, initial grade and how many levels of slip and finally on the sagittal vertical axis and its distance from the posterior superior corner of sacrum.